P166 Increasing screening frequency in men who have sex with men (MSM): impact of explicit guidance on risk profiling on UK service. (23rd May 2012) - Baker, A; Fleury, C; Foley, E; Samraj, S; Rowen, D; Patel, R
Abstract : Background: STI and HIV diagnoses are increasing among MSM. Mathematical modelling shows increasing screening frequency can reduce STI prevalence, especially targeting MSM engaging in risk behaviours. International guidelines from both the CDC and Australasian Society for HIV Medicine clearly define risk behaviours with adapted screening intervals—contrary to the UK where NICE guidance is vague. Objectives: To investigate impact of applying stricter international screening guidelines for MSM, on service workload and earlier STI diagnosis in a UK level 3 service [L-3S]. Methods: A validated risk questionnaire distributed to MSM attending a large provincial L-3S over a 3-month period explored their actual screening frequency, STI diagnoses and risk behaviours in the prior 12 months. Australian screening guidelines were applied to the data to identify MSM needing more frequent screening. Projections to the larger MSM population attending over 12 months were modelled, based on the demographics of the respondents. Results: 126/357 completed the questionnaire, 89 were identifiable. There was no statistically significant difference between STI rates (p=0.18) and HIV diagnoses (p=0.62) between identifiable questionnaire respondents and other MSM clinic attendees. Demographic analysis showed the sample group was representative of the larger cohort. In 2011, applying Australasian Society for HIV Medicine risk profiling for the 793 MSM who attended the unit, 26% would require one additional 6-monthly attendance for HIV screening, while 6% would require two visits. Additional STI screening visits would be needed by 25% (1 visit) and 10% (2 visits). 29% of STI diagnoses were in infrequent attendees. Conclusions: Stricter UK screening guidelines for MSM defining and weighting risk behaviours explicitly in line with other international guidelines, would increase L-3S MSM visits by 30% and potentially diagnose a large proportion of disease earlier. In light of the results UK guidelines may benefit from review.